EFFECTIVENESS OF AL-TAʿBIR AL-ḤURR METHOD IN ENHANCING ARABIC SPEAKING SKILLS - Alief, Muhammad; Mujahida, Anni; Elegbede, Nourouddine (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to assess the efficacy of the Al-Ta'biir al-Ḥurr (Free Expression) approach in enhancing Arabic speaking abilities among eleventh-grade pupils at MA Nurul Haromain, Yogyakarta. The research, which employed a quantitative method with a pre-experimental One-Group pre–test–post–test design, included 30 students whose speaking performance was evaluated using a rubric that included fluency, grammatical correctness, vocabulary, and speaking confidence. The Wilcoxon Signed-Rank Test and normalized gain (N-gain) analysis were used to evaluate the data. The findings showed a statistically significant improvement in students' Arabic-speaking skills, with a high N-gain score of 0.8268. According to these results, the Al-Taʿbīr al-Ḥurr approach promotes the Development of students' speaking abilities by encouraging active participation and unprompted oral expression. Generally speaking, the research indicates that this method might be used as a learner-centered teaching strategy to improve Arabic speaking abilities in classroom environments